The Degree of Health Awareness Among Kindergarten Teachers in Light of The Pandemic COVID-19 A field study on governmental kindergartens in Damascus (Journal of Hama University, 2021)
This study aimed to know the degree of health awareness among kindergarten teachers in light of the COVID-19 pandemic, and to achieve the goal of the study, the researcher prepared a questionnaire consisting of two parts: The first section included personal data, and the second section consisted of (39) items divided into four axes: Health Personality, appropriate healthy nutrition to prevent corona virus, practicing sports activities, healthy habits, and the questionnaire was applied to a sample of (66) teachers during the first semester of the academic year 2020-2021.The results of the study showed: that the degree of health awareness was high in general, while the degree of awareness of the dimensions of health awareness was as follows: personal health is high, healthy nutrition is moderate, practicing sports activity is moderate, health habits are moderate, according to the key correction adopted in the study.The results of the study did not show the existence of statistically significant differences between the mean scores of kindergarten teachers about the degree of their health awareness due to the scientific qualification or teaching experience variable. While the results showed that there are statistically significant differences between the mean scores of kindergarten teachers about the degree of their health awareness due to the variable of the presence of children in favor of the teachers who had children.